Evaluation of an Australian domestic abuse program for offending males. Issue 1 (11th January 2016) - Blatch, Chris; O'Sullivan, Kevin; Delaney, Jordan J; van Doorn, Gerard; Sweller, Tamara
Abstract : Purpose: – The purpose of this paper is to determine recidivism outcomes for 953 offending men with domestic violence histories, serving community-based sentences and enroled in the domestic abuse program (DAP), provided by Corrective Services New South Wales in Australia. Design/methodology/approach: – An intention to treat definition of DAP participation and a quasi-experimental and pseudo-prospective research design compared recidivism outcomes of the treatment group to a propensity score matched control group. Cox and Poisson regression techniques determined survival time to first reconviction and rates of reconvictions adjusted for time at risk. Findings: – DAP enrolment was associated with significant improvements in odds of time to first general reconviction (15 per cent) and first violent reconviction (by 27 per cent) compared to controls. Reconviction rates were significantly lower (by 15 per cent) for DAP enrolees. Programme completion was necessary for significant therapeutic effect; 62 per cent completed the programme. Practical implications: – This evaluation suggests the 20 session DAP is an effective intervention which could be adopted by other jurisdictions to modify criminal behaviours of domestically abusive men; potentially lessening the physical, emotional and financial impacts on victims and providing savings to government and criminal justice systems. The methodology, with refinements, could be adopted by other service providers to evaluate similar community-based therapeutic interventions in forensic settings. Originality/value: – First peer reviewed evaluation of the DAP. The programme contributes to evidence-based best practice interventions for domestically violent men.